Ibn Jama’ah: Reaktualisasi Pendidikan Karakter Khazanah Islam Klasik - Hadi, Muhammad Fazlurrahman (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2020)
The three major sins of national education conveyed by the Minister of Education and Culture, Nadiem Makarim, namely: bullying, sexual violence, and intolerance. This is a big problem that has never been found the right formula to be implemented in our education. In this study, it aims to invite educators and education experts, especially Islamic education, to find or offer the concept of character education that has actually been carried out by salaf scholars (formerly) in educating their students, so that they can answer the three problems above. The methodology of this research is literature review, with a descriptive-qualitative approach. The findings of this discussion include: Ibn Jama'ah had already applied the educational model to Sibyan - now known as Early Childhood Education (PAUD) - rather than Western education figures. In addition, he emphasized the need for student etiquette to himself, his teacher and the knowledge he was learning. Therefore, it is important and urgent to re-actualize and reopen literacy of classical Islamic treasures that are no less than Western literacy as a basic concept of thinking about character education. Another thing that is no less important, is that character education does not need to be a separate subject or course, because character education should be integrated or integrated with other subjects